Purification and characterization of the in vitro activity of I-Sce I, a novel and highly specific endonuclease encoded by a group I intron. - Monteilhet, C (1990)
Group I intron encoded proteins represent a novel class of site specific double strand endonucleases. The endonuclease activity of this class of proteins has been first demonstrated in vivo for I-Sce I which is encoded by a mitochondrial intron of Saccharomyces cerevisiae. Assays using crude cell extracts have shown that I-Sce I can be used in vitro as a restriction endonuclease potentially useful for recombinant DNA technology owing to its large recognition sequence (18 nucleotides). We report here the purification and the first detailed analysis of the in vitro activity and properties of I-Sce I.